Metode Tafsir Hamka dalam Tafsir Al-Azhar - Ananda Rizki Prianka Putri; A. Halil Thahir; Robingatun Robingatun; Khaerul Umam (Gunung Djati Conference Series, 2023)
This study aims to discuss the interpretation method used by Hamka in Tafsir Al-Azhar. This study uses a qualitative approach by applying descriptive analytical methods. The formal object of this research is the method of exegesis used by Hamka in his commentary book, while the material object is Tafsir Al-Azhar which is studied using the method of exegesis. The results of the research and discussion show that the method of interpretation used by Hamka in Tafsir Al-Azhar is based on the source, namely a combination of the bil ma'tsur method and the bil ra'yi method, while based on the target verse Hamka uses the tahlili method and the tafshili method in terms of explaining the interpretation.